Impossible wardrobes [catalog of exhibitions held at the Palais de Tokyo, 2012 ; the École Nationale Supérieure des Beaux-Arts de Paris, 2013 ; the Palais Galliéra, 2014 - Swinton, Tilda 1960-; Saillard, Olivier 1967-
"This lavish three-book set presents the three performance pieces that spanned a period of three years. In The Impossible Wardrobe (2012), Swinton walks down a runway with a selection of historically and culturally significant garments from the past 200 years. In Eternity Dress (2013), a garment is tailor-made in front of a live audience. And in the third performance in the series, Cloakroom (2014), Swinton examines the special relationship between an item of clothing and its owner. A glorious ode to fashion, Impossible Wardrobes presents and elevates couture to a veritable art form."--Publisher's website
Titel vom Schuber
Keywords: Swinton, Tilda / Exhibitions; Swinton, Tilda; Swinton, Tilda -- 1960-; Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1800-; Geschichte 2012-2014; Fashion in art / Exhibitions; Performance art / Exhibitions; Clothing and dress in art / Exhibitions; Fashion / History / 19th century / Exhibitions; Fashion / History / 20th century / Exhibitions; Clothing and dress in art; Fashion; Fashion in art; Performance art; Geschichte; Kleidung; Modeschau; Performance -- Künste; Mode; Paris; Ausstellungskatalog; Bildband